Liquiritin inhibits H2O2‐induced oxidative stress injury in H9c2 cells via the AMPK/SIRT1/NF‐κB signaling pathway. Issue 10 (5th August 2022) - Tang, Tong‐Juan; Wang, Xiang; Wang, Liang; Chen, Ming; Cheng, Jing; Zuo, Meng‐Yu; Gu, Jin‐Fan; Ding, Rui; Zhou, Peng; Huang, Jin‐Ling
Abstract: Heart failure (HF) is a serious disease with high mortality. Oxidative stress plays a vital role in its occurrence and development. Licorice is commonly used to treat HF in traditional Chinese medicine. Liquiritin, the main ingredient of licorice, has antioxidant and anti‐inflammatory properties, but the mechanism against oxidative stress in cardiomyocytes has not been reported. Establishment of oxidative damage model in H9c2 cells by hydrogen peroxide (H2 O2 ). Liquiritin (5, 10, 20 μmol/L) could significantly prevent the loss of cell viability and decrease the apoptosis rate. It can reduce the levels of reactive oxygen species (ROS), malonedialdehyde (MDA), lactate dehydrogenase (LDH), tumor necrosis factor‐alpha (TNF‐α), interleukin‐1β (IL‐1β), interleukin‐6 (IL‐6), and increase the activity of ATP, superoxidedismutase (SOD), glutathione peroxide (GSH‐px), glutathione reductase (GR) and catalase (CAT) to alleviate oxidative stress and inflammation in a dose‐dependent manner. Liquiritin was found to be related to AMP‐Activated Protein Kinase (AMPK) pathway by molecular docking. Western blotting (WB) and quantitative reverse transcription PCR (RT‐qPCR) confirmed that liquiritin could promote AMPKα phosphorylation and sirtuin 1 (SIRT1) protein expression, and inhibit phosphorylation of nuclear factor kappa B p65 (NF‐κB p65). Compound C, EX 527, and PDTC can reverse the effects of liquiritin, indicating that its antioxidant effect is achieved by regulating AMPK/SIRT1/NF‐κB signaling pathway. Practical applications: Heart failure is one of the most common cardiovascular diseases, and its treatment remains a worldwide problem. Licorice is a food and dietary supplement that has been used widely in traditional Chinese medicine (TCM). Liquiritin is one of the main active components of licorice, which has antioxidant and anti‐inflammatory pharmacological effects. This study revealed the mechanism of licorice against oxidative damage of H9c2 cardiomyocytes, and provided a scientific basis for liquiritin as an antioxidant in the treatment of heart failure. Abstract : The mechanism of liquiritin againsts oxidative stress was studied by molecular docking and in vitro experiment. The results showed that liquiritin attenuated the oxidative stress injury of H9c2 cells induced by H2 O2 through AMPK/SIRT1/NF‐κB signaling pathway, suggesting that liquiritin has a potential role in preventing and treating heart failure.